Efektifitas Instalasi Pengolahan Air (IPA) Unit 2 Tirta Kencana PDAM Kota Samarinda Terhadap Kualitas Air Minum Tahun 2015 - Anrianisa dan FL. Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
The aim of this research is to know the process of the cultivation of the clean water. The research is held in PDAM Samarinda. There are two kinds of the process namely (Complete Treatment Process) covering physics, chemistry, bacteriology and and the Partial Treatment Process. Whereas the the clean water cultivation consists of some buildings water catch presidementasion, pulsator, coagulation, speed blendering, flocking, filtrision reservoir (desinfection), clean water pump, and lagoon. The standard of the water quality based on the regulation No.492/MENKES/PER/IV/2010 dated on April the 19th 2010 which arranged the requirements of the drinking water and the controlling as well which is based on the Indonesian National standard. Based on the SNI covering temperature, colour, taste, and the darkness. The quality of the chemistry such as mercury, Arsen, Iron, Fluoride, Cadmium, chlorida, Zinc, mangaan, pH, ammonia and Carbon dioxide Where as for the microbiology covering bactery and virus. The standard Based on the Ministery of Health No. 416/MENKES/PER/IX/ by giving the narration that the water does not disturb the health, illness, technical disturbance and the handicap of estetic. The recommendation is that the drinking water has to be hygienic.